Fairtrade, agrochemical input use, and effects on human health and the environment - Jorge Sellare; Eva-Maria Meemken; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2020)
It is often assumed that voluntary sustainability standards - such as Fairtrade - could not only improve the socioeconomic wellbeing of smallholder farmers in developing countries but could also help to reduce negative health and environmental impacts of agricultural production. The empirical evidence is thin, as most previous studies on the impact of sustainability standards only focused on economic indicators, such as prices, yields, and incomes. Here, we argue that Fairtrade and other sustainability standards can affect agrochemical input use through various mechanisms with possible positive and negative effects. We use data from farmers and rural workers in Cote d'Ivoire to analyze effects of Fairtrade certification on fertilizer and pesticide use, as well as on human health and environmental toxicity. Fairtrade increases chemical input quantities and aggregated levels of toxicity. Nevertheless, Fairtrade reduces the incidence of pesticide-related acute health symptoms among farmers and workers. Certified cooperatives are more likely to offer training and other services related to the safe handling of pesticides and occupational health, which can reduce negative externalities in spite of higher input quantities. These results suggest that simplistic assumptions about the health and environmental effects of sustainability standards may be inappropriate.
Keywords: O12; Q01; Q12; Q13; 330; Agrochemicals; certification; Fairtrade; pesticides; sustainability standards; toxicity